Impact of Concrete Quality on Sustainability. (2015) - Kusuma, Gideon H.; Budidarmawan, Johannes; Susilowati, Ani
Abstract: With the increased focus on sustainable construction, building products are being required to document the environmental impact associated with their manufacture and show continuous improvement. This article focuses on the concrete mixture and demonstrates how improved concrete quality can play an important role in developing concrete products with reduced environmental impact and contribute to sustainable development. Improved concrete quality practices and lower standart deviations of compressive strength result required average strength for a specified strength. The carbon footprint for the producer with S = 8.6 MPa, was calculated to be about 41% higher than that for the producer with S = 2.4 MPa. Improved job-site cylinder curing practices can contribute to sustainability. Concrete mixtures can be optimized to contain low cementitious content with a target w/cm the lowest amount of mixing water content for a 12.5 mm slump be used and higher workability levels can be attained with admixtures dosages. Proper maintenance of plant and mixers ensures reduced energy and waste, tracking concrete and ambient temperatures at the plant can help reduce the energy for heating and cooling the concrete. Monitoring batching accuracy ensures conservation of materials while reducing the variability of the concrete produced. This helps sustainability through reduced energy use in handling rejected concrete, supplying new concrete as a replacement, lowering the amount of coring, and lowering the amount of repair material. At this time, standard deviation in Indonesian concrete industry still high, therefore, opportunities for improvement of the quality and sustainability of concrete in Indonesia are very big.